DEVELOPMENT OF A PARTICIPATORY LEARNING MODEL TO INCREASE INTEREST IN LEARNING SOCIAL SCIENCES - Miftachul Amri (CV. ADIBA AISHA AMIRA, 2023)
This literature review discusses the development of a participatory learning model to increase interest in learning social sciences. Participatory learning activities as a new model in the educational process emerged in higher education units in the seventies and are flexible and open to further development. This characteristic is an opportunity for students to strive to develop principles, methods and techniques that are suitable for use in participatory learning. Participatory learning is expected to be able to increase students' involvement in the learning process, students are given the freedom and breadth to develop their potential. This is to increase student interest in learning and student activity in learning. So that students will understand and apply it in everyday life and can have implications for increasing students' interest in learning in Social Sciences subjects. In this learning, principles are used, namely based on learning needs, oriented to the goals of learning activities, based on experience, centered on learning citizens. Efforts to implement participatory learning can be emphasized by emphasizing the role of education to help students carry out active and participatory learning activities in Social Sciences lessons.